Factors influencing decisions to invest in cryptocurrency - Bland, Austin S (East Carolina University, 2022)
Cryptocurrency is one of the newer options when it comes to the world of investing. According to a survey done by Bakkt, a digital asset marketplace, 48 percent of American investors invested in cryptocurrency during the first half of 2021, and 32 percent of respondents who did not currently hold cryptocurrency planned to within the next 6 months. This relatively new investment method has gained a lot of interest from investors. For all the excitement around cryptocurrencies, we know very little about this investment method. There has not been much research done on the issue of how risky investors perceive cryptocurrency to be, or what drives risk tolerance when dealing with cryptocurrency investments. This study investigates whether the source and amount of investment capital will influence the desire to invest in cryptocurrency and the perceived risk of investing in cryptocurrency. I find that participants with self-generated capital choose to invest less in cryptocurrency when the dollar amount available to invest is $1,000.
Keywords: Cryptocurrency; Risk Perception; Investments